Campo natural sob diferentes intensidades de pastejo: diversidade florística e dinâmica de Desmodium incanum (Sw.) DC. - Bolzan, Cassiane Soares (2022)
The basis of livestock production in the state of Rio Grande do Sul is the natural grasslands shaped into different structures and physiognomies due to the high diversity of species. The exploration of these environments by herbivores is complex and the botanical richness is the main challenges for foraging. Since disturbance intensities affect the structure and composition of vegetation, the objective of this study was to verify the diversity of species, with emphasis on legume richness and the dynamics of Desmodium incanum (Sw.) DC., an exponent and widely dispersed species in this region, environment, under different forage supply gradients (4, 8, 12 e 16% FS), which consequently result in different grazing intensities (high, moderate and low) in a natural grassland in the central depression of the state of Rio Grande do Sul- Brazil, subjected to bovine herbivory for 35 years. The experimental area is located in the Agronomic Station of the Federal University of Rio Grande do Sul in the municipality of Eldorado do Sul-RS. Eight sampling units (packets) were used in the gradients of forage supply (FS) and different grazing intensity (4% FS - high grazing intensity, 8% FS and 12 % FS moderate grazing intensity and 16 % FS low grazing intensity). The vegetation was inventoried through floristic and phytosociological surveys (October and December 2020, February and April 2021). A total of 162 species were recorded in the evaluated period, distributed in 39 families, from these, 17 are legume species. The legume species with the highest importance value index (IVI) in all treatments was Desmodium incanum. There was a difference (p<0.05) for the Shannon and Wealth indexes, both higher in moderate grazing intensities (8 and 12% FS). In the verification of the dynamics of Desmodium incanum legumes was the object of study and we concluded that the population of Desmodium incanum is affected by grazing intensities in terms of abundance (higher in high intensity- 4% FS) and exposure in the canopy (inside and outside of tussock), on the other hand, the architectural presentation (erect/prostrate) is affected by the reliefs (lowered, back and top). The results of floristic diversity corroborate other studies that emphasize that at moderate grazing intensities, they provide pasture structures that optimize intake and are beneficial to the ecosystem (e.g.increase in biodiversity). The legume Desmodium incanum is shown to be a key species for the composition of high biological value diets (secondary compounds and high protein value) of herbivores in all pasture structures.